2009
DOI: 10.1016/j.acap.2009.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Yoga for the Pediatric Population: A Systematic Review

Abstract: Objective-Evaluate the evidence for clinical applications of yoga among the pediatric population.Methods-We conducted an electronic literature search including CINAHL, Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE, Medline, PsycINFO, and manual search of retrieved articles from inception of database until December 2008. Randomized controlled trials (RCTs) and non-randomized controlled trials (NRCTs) were selected including yoga or yoga-based interventions for individuals aged from 0 to 21 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
1
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(132 citation statements)
references
References 49 publications
3
118
1
6
Order By: Relevance
“…Twenty-nine articles were excluded because of the following: adult study population (n = 6), irrelevant outcome measures, such as improvement in rectal sensitivity or gastrointestinal symptoms without abdominal pain (n = 2), no systematic review or RCT (n = 15), or inclusion only of trials that were already included by another systematic review (n = 6). Thirteen articles remained for analysis: 7 systematic reviews 11,12,15,16,18,22,23 (including 18 RCTs) and 6 RCTs. [24][25][26][27][28][29] Two included trials concerned follow-up studies, 26,30 which will be discussed by using their original studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-nine articles were excluded because of the following: adult study population (n = 6), irrelevant outcome measures, such as improvement in rectal sensitivity or gastrointestinal symptoms without abdominal pain (n = 2), no systematic review or RCT (n = 15), or inclusion only of trials that were already included by another systematic review (n = 6). Thirteen articles remained for analysis: 7 systematic reviews 11,12,15,16,18,22,23 (including 18 RCTs) and 6 RCTs. [24][25][26][27][28][29] Two included trials concerned follow-up studies, 26,30 which will be discussed by using their original studies.…”
Section: Resultsmentioning
confidence: 99%
“…One study of the systematic review by Birdee et al 23 was included regarding alternative therapy. Kuttner et al 50 compared 14 children receiving yoga versus 11 wait-list control subjects.…”
Section: Alternative Medicinementioning
confidence: 99%
“…17) Several studies report that various stresses from the uncertainty about the future, going to college, grades on the tests and low physical activity induced by studying all day, no break. 15,16) In other studies on yoga for high school student, many have cited stress reduction, and many have used yoga to manage negative emotions such as depression, anxiety, and anger, and some stated that more happiness, calmness, and a sense of refreshment were propagated. 12,13) These results suggest that school-based yoga programs may be appropriate for promoting health by focusing on the prevention of negative patterns during the transition of adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…12) Remarkably, some studies have reported that the practice of yoga helps to reduce stress related to academic performance, increases self-esteem and self-regulation and promotes healthy behaviors in adolescents. [12][13][14][15][16] High school students in Korea are a health risk group under a lot of stress from preparing for the scholastic aptitude test or finding jobs, and they have the risk of low physical activity and irregular eating habits as well as a lack of sleep and high health risk behaviors such as smoking, drinking alcohol. 17) The choice of an unhealthy life style made by many adolescents has resulted in chronic conditions such as cardiovascular diseases, cancer, obesity and type 2 diabetes after the transition to adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation